Antilocution and trust in the workplace: Perceptions of higher education trained police recruits in England and Wales. (11th February 2022) - Rogers, Colin; Turner, James; Birch, Philip
Abstract: This study seeks to examine the relationship between antilocution and trust in the workplace by reflecting on the perceptions of police officers who are undertaking the new Higher Education (HE) pathway into the policing profession in England and Wales. This relationship is considered through Allport (1979) . 'The Nature of Prejudice. New York, NY: Perseus' concept of antilocution and the lens of trust in the workplace, to understand how new police students think they are regarded by their policing colleagues and its impact on practice. Utilizing a survey of police students from five different forces in England and Wales, indicative results suggest that, whilst broadly supportive of new police officers, there may be some division regarding their education and training pathway through higher education, engendering levels of prejudice and bias towards the new recruits. Police student responses indicate that many of them feel that more is expected of them and that they are under closer supervision because they have undertaken the Higher Education route. Arguably, this prejudice and bias have an adverse effect on trust within the workplace, a concept which is front and centre of policing which ultimately can have a negative impact on public safety and security. The results of this study indicate that the interaction between new recruits (out-group) and established colleagues (in-group) is complex and not straightforward, and suggested implications for police practice are presented.